The Implementation of the Maslahah Principle in Cultivating Religious Moderation in the State Islamic Universities - Mukri, Moh.; Hermanto, Agus; Hanif, Hanif; Susanto, Is; Rochmad, Rochmad (al-'adalah, 2024)
Higher education is an effective means of transforming thought and movement to counteract the negative influence of various extreme and deviant religious schools and understandings, one of which is radical ideology, which has recently begun to emerge among students at several tertiary institutions. This study aims to obtain an overview of the steps that have been taken by UIN Raden Intan Lampung, UIN Sunan Ampel Surabaya, and UIN Sunan Gunung Jati Bandung in grounding the concept of religious moderation to anticipate and counteract the radicalism ideology that has recently infiltrated among University students. This research is classified as descriptive qualitative field research, using the maslahah (benefit) theory. Data were obtained from reviewing several documents in the three institutions, which were then processed and analyzed using the content analysis method. This study concludes that although each University has a different approach in its efforts to prevent and overcome radical religious ideology, the concept offered is the same, namely religious moderation, which is based on the principle of welfare, namely “li jalbi al-mashālih wa li daf'i al-mafāsid” (taking benefit and eliminating harm).